Social Communication Patterns of Silver Man in Daily Life in South Tangerang City - Pratama, Bintang; Hendrawan, Hendri; ., Indriastanto; Parengkuan, Pricilia; Sofiana Sari, Syifa (KnE Social Sciences, 2023)
The silver man phenomenon in South Tangerang City is quite troubling. In addition to impacting the perpetrator, this silver man’s existence indirectly disturbs the order on the highway. This fact is certainly interesting if you look more closely at the actual conditions and the appearance of the silver man, who seems complicated to take firm action against. This study discusses the Silver man’s social communication pattern in daily life in the City of Tangerang. The researcher used descriptive qualitative research with a qualitative approach. The data needed to describe the Silver Man communication pattern in South Tangerang City were obtained using in-depth interviews, observation, and document review techniques. From the analysis of this study, it was found that first, social communication took place in the form of individual communication with other silver people using regionaland non-verbal languages. The second is that social communication also takes place in the form of personal communication with parents and siblings. Keywords: community communication, communication pattern, silver man